Kiedy parametry modelu GARCH wymagają ponownej estymacji? - Galin, Kamila (When Garch Parameters Need to Be Reestimated?, 2008)
n the first part of the article, it is shown that a change in one GARCH parameter may lead to false parameters estimation results. A method of detecting GARCH parameters changepoint is presented in the next part of the paper. The method is tested on artificially generated time series and is applied to detect the first parameters changepoint in the rates of return of the WIG index.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 18, s. 28-37